2021
DOI: 10.1038/s41419-021-04157-x
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 21 (FGF21) alleviates senescence, apoptosis, and extracellular matrix degradation in osteoarthritis via the SIRT1-mTOR signaling pathway

Abstract: Osteoarthritis (OA) is a complex condition that involves both apoptosis and senescence and currently cannot be cured. Fibroblast growth factor 21 (FGF21), known for its role as a potent regulator of glucose and energy metabolism, protects from various diseases, possibly by mediating autophagy. In the present study, the role of FGF21 in the progression of OA was investigated in both in vitro and in vivo experiments. In vitro, the results revealed that FGF21 administration alleviated apoptosis, senescence, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 53 publications
1
22
0
1
Order By: Relevance
“…In the DMM (destabilization of the medial meniscus) model for OA, treatment with FGF21 reduced OA phenotypes. In vitro, FGF21 protected chondrocytes from apoptosis, senescence, and ECM catabolism in response to oxidative stress (Lu et al, 2021).…”
Section: Selected Topics In Genetics Development Regeneration and Dis...mentioning
confidence: 99%
“…In the DMM (destabilization of the medial meniscus) model for OA, treatment with FGF21 reduced OA phenotypes. In vitro, FGF21 protected chondrocytes from apoptosis, senescence, and ECM catabolism in response to oxidative stress (Lu et al, 2021).…”
Section: Selected Topics In Genetics Development Regeneration and Dis...mentioning
confidence: 99%
“…Fibroblast growth factor 21 (FGF21) is a secreted endocrine factor that acts as a pivotal regulator of metabolic function [ 1 ]. FGF21 has been indicated to be implicated in a diversity of biological processes, such as autophagy and apoptosis [ 2 , 3 ]. FGF21 alleviates endoplasmic reticulum stress-induced apoptosis to mitigate vascular calcification in rats [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that Sirt1 could activate autophagy through a variety of pathways, including regulation of fox headbox transcription factor (FOX), ATG5, ATG7, LC3, and Beclin1 [ 47 , 48 ]. FGF21-induced autophagy flux enhancement was mediated by the nuclear translocation of TFEB, which occurs due to the activation of the Sirt1-mTOR signaling pathway [ 49 ]. In this study, we found that PTUPB can stabilize Sirt1 protein in liver and hepatocytes.…”
Section: Discussionmentioning
confidence: 99%